Increased mean platelet volume in patients with vestibular migraine - Çavuş, Mehmet Emin; Tanyeli, Talip Talha; Akcan, Fatih Alper; Bayır, Ömer; Gökkurt, Didem (The European Research Journal, 2020)
Objectives: The purpose of this study was to investigate relation between mean platelet volume, platelet distribution width, platelet-to-lymphocyte ratio, neutrophil-to-lymphocyte ratio and vestibular migraine.Methods: This study was planned in prospective manner and conducted in Ankara Polatlı State Hospital between April 2017 and May 2018. Thirty patients diagnosed with vestibular migraine and thirty healthy, age and sex-matched subjects were enrolled to the study. Mean platelet volume, platelet distribution width, platelet count, neutrophil count and lymphocyte count in blood samples were measured.Results: The mean age of the patients with vestibular migraine was 39.90 ± 7.16 and the study group consisted of 11 males and 19 females. The mean platelet volume and platelet distribution width values in patients with vestibular migraine were significantly higher than the control group (p < 0.001). There were no difference on mean neutrophil/lymphocyte ratio and platelet/lymphocyte ratio values between patient group and control group. Conclusions: We found a positive relation of increased levels of mean platelet volume and platelet distribution width with vestibular migraine. Higher mean platelet volume is associated with atherosclerosis and thromboembolism. Vascular pathologies are blamed for both headache syndromes like migraine and vertiginous syndromes. This theory supports our study but pathophysiological mechanism is not clear.